WWOX-Related Neurodevelopmental Disorders: Models and Future Perspectives - Daniel J. Steinberg (MDPI AG, 2021)
The WW domain-containing oxidoreductase (WWOX) gene was originally discovered as a putative tumor suppressor spanning the common fragile site FRA16D, but as time has progressed the extent of its pleiotropic function has become apparent. At present, WWOX is a major source of interest in the context of neurological disorders, and more specifically developmental and epileptic encephalopathies (DEEs). This review article aims to introduce the many model systems used through the years to study its function and roles in neuropathies. Similarities and fundamental differences between rodent and human models are discussed. Finally, future perspectives and promising research avenues are suggested.